2022
DOI: 10.1002/fsn3.2472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air fryer frying temperature on the quality attributes of sturgeon steak and comparison of its performance with traditional deep fat frying

Abstract: In this study, the influence of air‐frying temperature on the physical properties of sturgeon steaks was explored. Meanwhile, the comparison of traditional deep fat frying (TF) and air fryer frying (AFF) methods on the quality, flavor, and digestibility of sturgeon steaks were investigated. The results indicated that along with the increase of temperature (130, 160, and 190℃) for 15 min, the moisture content of AFF sturgeon steak surface decreased dramatically while that of interior was well preserved. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Heating oils may result in elevated levels of PAHs [ 30 , 31 ]. Air frying, compared to microwave and low-pressure frying, replicates the heat flow akin to boiling oil, dehydrating the food and allowing meat to be cooked with minimal or no additional oil, resulting in significantly reduced fat absorption [ 1 ]. Furthermore, the findings of this study revealed that BaP was undetectable in all cooked beef patties prepared without oil brushing, suggesting that oil-free cooking can effectively mitigate BaP concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heating oils may result in elevated levels of PAHs [ 30 , 31 ]. Air frying, compared to microwave and low-pressure frying, replicates the heat flow akin to boiling oil, dehydrating the food and allowing meat to be cooked with minimal or no additional oil, resulting in significantly reduced fat absorption [ 1 ]. Furthermore, the findings of this study revealed that BaP was undetectable in all cooked beef patties prepared without oil brushing, suggesting that oil-free cooking can effectively mitigate BaP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The air fryer is a novel cooking appliance that has emerged in recent years, which replaces hot oil with heated air to achieve the frying effect [ 1 ]. Compared with the oven, a common traditional cooking appliance, the air fryer produces fewer chemicals and carcinogens because it uses oil-free cooking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The circulation of hot air accelerates the oxidation process of food, giving it an excellent flavor. Meanwhile, the high temperature dehydrates the surface of the food quickly, creating a crusty layer to preserve the moisture inside the food ( Liu et al, 2022b ). Microwave treatment depends on the action of electromagnetic fields that make the water molecules inside the food crash to produce heat energy.…”
Section: Introductionmentioning
confidence: 99%